LEARNING ORIENTATION, ENTREPRENEURIAL ORIENTATION, INNOVATION AND THEIR IMPACTS ON NEW HOTEL PERFORMANCE: EVIDENCE FROM SURABAYA - Oktavio, Adrie; Kaihatu, Thomas Stefanus; Kartika, Endo Wijaya (Universitas Brawijaya, Indonesia, 2019)
Based on investor perspective, Surabaya city is still recognized as a promising investation land especially in the tourism industry. As can be seen based on recent last three years, whereas a lot of new hotel establishment is introduced. The presence of these new hotel establishments could be the indicator of tourism and economic growth in Surabaya city. However, growth may also lead to tighter competition. Therefore, to competitively compete during its early years, new hotel establishment should have a strategic orientation within its business operations with additional innovation breakthrough to create value or a competitive advantage. New hotel establishment also should maintain its good performance. This research is conducted to observe the implementation of Strategic Orientation, especially related with Learning Orientation and Entrepreneurial Orientation which is conducted by the establishment to achieve a better performance, which is also supported by the predesigned innovative programs. The empirical result based on 49 new hotel establishment in Surabaya city as the research sample, indicated indirect relationship between Learning Orientation and Entrepreneurial Orientation to performance with innovation as the mediator. It is suggested to add Market Orientation as the intervening variables for the future research especially regarding the role of Strategic Orientation and Innovation in new hotel establishments due to their infancy stage.